Reduced sympathetic outflow and adrenal secretory activity during a 40-day stay in the Antarctic - S. Farrace; M. Ferrara; C. De Angelis; R. Trezza; P. Cenni; A. Peri; CASAGRANDE, Maria; DE GENNARO, Luigi (International Journal of Psychophysiology, 2003)
Human adaptation to unknown and extreme environments requires changes in the psychological and physical homeostasis. We previously reported a significant decrease of anterior pituitary and adrenal hormonal levels and a significant modification of psychophysiological correlates of stress, such as galvanic skin response, after exposure to Antarctica, suggesting a possible decrease of individual arousal. The latter was hypothesized to be correlated with a modification of autonomic balance, mainly represented by a possible reduction of adrenergic output. The aim of the present study was to assess the patterns of hormonal circadian rhythms and the autonomic nervous system balance by means of spectral analysis of heart rate variability (HRV). These parameters were evaluated during 3 sessions (baseline, session I and session 2), before, at the beginning and after a 40-day stay in Antarctica (Station of Terra Nova Bay; average temperature in the study period: - 11 degreesC, 24 h of light, sea level). In each of the sessions, 6 healthy male subjects underwent a 24-h electrocardiogram and blood sampling (08.00, 12.00, 16.00, 20.00, 24.00 and 08.00 h) for hormonal determinations. The data showed a remarkable decrease of hormonal levels without significant changes in circadian rhythms. Spectral analysis of HRV showed an imbalance of the autonomic nervous system with a relative significant decrease of the low frequency band (0.1 Hz) in session I and 2 compared to baseline, which can be functionally interpreted as a relative decrement of the sympathetic component. In conclusion, the exposure to a cold and extreme environment seems to affect autonomic balance over a 40-day period. This is followed by a significant reduction of the anterior pituitary and adrenal hormonal secretory patterns with preserved hormonal circadian rhythms (within the same time period of 40 days). This pattern is suggestive of a trophotropic neurovegetative adaptive process. (C) 2003 Elsevier Science B.V. All rights reserved.